The impact of COVID-19 and Ukraine war on the global business environment - Bejček, David (2023)
The aim of this study is to investigate the impact of the COVID-19 pandemic and the Russian invasion of Ukraine on the global business environment by examining how these crisis events affected financial markets, which is an essential concern for managers around the globe. The research begins with a thorough literature review, followed by the explanation of the data collection and methodology of the research. The study applies a quantitative analysis using primary and secondary data, comprising of a survey and volatility analysis. This enabled to obtain both subjective and objective results for comparison. The findings highlight the need for businesses to be adaptive, innovative, and informed when responding to crises. Results also emphasise the need for policy-makers to enhance individuals’ financial literacy to cultivate trust, which is essential for driving future economic recovery and fostering prosperity.